The experiences of couples undergoing Preimplantation Genetic Diagnosis (PGD) at the Genetic and Developmental Medicine Clinic, Sultan Qaboos University Hospital (SQUH) in Oman - Al-Kharusi, Khalsa (Division of Human Genetics, 2017)
Preimplantation genetic diagnosis (PGD) is an alternative reproductive technology integrated with in-vitro fertilisation (IVF). It is a well-established technique offering reproductive options for families at a high risk of transmitting a genetic disorder, allowing them to avoid a termination of pregnancy (TOP). Consanguineous unions are common and encouraged in many Arab communities. This can lead to an increased risk of one or more autosomal recessive disorders that may occur within the family. Traditional prenatal testing involves testing fetal cells with the option of TOP of an affected fetus. In Arab communities where TOP is restricted under Muslim law, such testing is not acceptable. For these couples and their family members, PGD is a feasible option as the fetus is diagnosed before implantation and allows for only healthy embryos to be implanted. However, undergoing PGD is relatively new in the Arabic Muslim countries and Omani patients have only recently had access to the service. This study utilised a phenomenological approach to explore the experience of Omani families who had selected to undergo PGD as a means of reducing the risk of having a child affected with a genetic disorder. Fourteen participants from eight families who underwent PGD were interviewed. Data collected were analysed using thematic analysis. The research identified five main themes; Desire for a Healthy Child; Anxiety "Taraqub"; Unforeseen; Secrecy; Me and My Partner. The PGD experience was reported as physically and emotionally distressing. Some participants felt attached to their embryos regardless of health status, while the majority did not anticipate the loss of intimacy, autonomy and control they experienced, particularly related to the insemination process. The social and religious background of participants played a significant role in the participant's perception of PGD, which has both practical and psychosocial implications. The findings of the research have provided insight into the PGD experiences of Omani families and can be used to improve the services that are currently available to these families.